Revival of the Heritage Using Porcelain Units Inspired by Traditional Sadou Decoration and Kufic Calligraphy in Fashion Design: تهاني ناصر العجاجي ---وجدان محمد الفليج (Al-Academy, 2019)
The purpose of this research is to identify heritage and highlight its value by drawing on its decorative vocabulary and integrating it with the Arabic calligraphy to revive the heritage in a contemporary style, and to create decorative design units inspired by Sadou and Arabic calligraphy and to employ them in the modern fashion designs. The applied descriptive approach has been used in this research, and the research community is made of women in Riyadh area. The tools used in this research were the questionnaire and the observation. The most important results of the research are: the design of decorative units from the integration of Arabic calligraphy and the decorations of the Saduo, and the use of these units in the design of the of women's fashion using the method of printing, and manual and automatic embroidery. The research has stressed the importance of integrating Saduo decorations with the calligraphy in raising the aesthetic value of the dress, and contributing to the revival of the heritage, and promoting the national identity through fashion. One of the most important recommendations in this research is to encourage local designers to use Arabic calligraphy, sadou decoration in fashion design, and textiles. The entities concerned with heritage events make exhibitions, and various presentations to identify heritage, especially folklore, and to increase interest in the study of Arabic calligraphy - with the artistic and aesthetic values that it has - in universities and academic programs through the inclusion of calligraphy and supporting the garment industry, and textiles inspired by Saudi traditional heritage to fit the modern era, while retaining its originality which would be helping to revive the heritage and promote the national identity of the members of society..